The Potential Utilization of Plastic Waste as a Building Material - Atmaja, Sang Kompiang Rizki Putra; Warmadewanthi, Idaa (International Journal Labs, 2023)
One of the innovations in utilizing plastic waste is to process it into Plastic Blocks for Wall Pairs (BPBPD). This research aimed to analyze the temperature required in melting used plastic and cooking oil for making BPBPD mixtures. Variations in the research are temperature under the range 180°C, 200°C, and 220°C. Comparison of the proportions of the mixture of plastic, oil, and coarse aggregate 5-10 mm, namely 1.5:1:0.5, 1:1:0.5, and 1:1:0.25. The types of plastic used are plastic bags, aluminum-coated plastic, and mica plastic. The parameters in this study are the compressive strength value, the initial rate of suction (IRS) value, the porosity value, and the water absorption rate. The study results showed that the minimum temperature for melting plastic bags and aluminum is 180°C, and for melting mica plastic is 220°C. The recommended proportion for making this BPBPD is a ratio of 1.5:1:0.5. The results of the IRS test on the plastic bags BPBPD ranged from 0.037-0.057 Kg/m2, the aluminum plastic BPBPD 0.030-0.057 Kg/m2, and the mica plastic BPBPD 0.033-0.043 Kg/m2. The water absorption rate for plastic BPBPD ranges from 0.233-0.378%, aluminum plastic BPBPD 1.644-4.233%, and mica plastic BPBPD 1.233-2.756%. Porosity results from the plastic bag BPBPD ranged from 0.355-0.931%, the aluminum plastic BPBPD 10.83-12.1%, and the mica plastic BPBPD 2.25-3.9%. In general, the compressive strength of BPBPD plastic bags, both without and with immersion, meets the minimum average compressive strength according to BSN 1989 with quality IV with the highest value in the 1.5:1:0.5 mixture of 38.2 Kg/cm2.